2012
DOI: 10.1088/0004-637x/750/1/79
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Velocities of Individual Components in Very Low Mass Binaries

Abstract: We present rotational velocities for individual components of 11 very low mass (VLM) binaries with spectral types between M7 and L7.5. These results are based on observations taken with the near-infrared spectrograph, NIRSPEC, and the Keck II laser guide star adaptive optics system. We find that the observed sources tend to be rapid rotators (v sin i > 10 km s −1 ), consistent with previous seeing-limited measurements of VLM objects. The two sources with the largest v sin i, LP 349−25B and HD 130948C, are rota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 80 publications
(168 reference statements)
9
65
0
Order By: Relevance
“…Given that we have shown that the component masses are within 2% of each other for this coeval, co-compositional binary system, one likely explanation for the divergent behavior is a difference in the angular momentum evolution of the two components. Projected rotational velocities (v i sin ) of other very-low-mass binaries have hinted at such differences in angular momentum evolution (e.g., Konopacky et al 2012), but such measurements have yet to be obtained for LSPMJ1314+1320AB. The components of LSPMJ1314+1320AB are now the nearest, lowest mass pre-main-sequence stars with direct mass measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Given that we have shown that the component masses are within 2% of each other for this coeval, co-compositional binary system, one likely explanation for the divergent behavior is a difference in the angular momentum evolution of the two components. Projected rotational velocities (v i sin ) of other very-low-mass binaries have hinted at such differences in angular momentum evolution (e.g., Konopacky et al 2012), but such measurements have yet to be obtained for LSPMJ1314+1320AB. The components of LSPMJ1314+1320AB are now the nearest, lowest mass pre-main-sequence stars with direct mass measurements.…”
Section: Discussionmentioning
confidence: 99%
“…We selected 18 bright (typically J < 14.1 mag) ultracool dwarfs with spectral types ranging from M7 through T2 and published projected rotational velocities, v sin i ≥ 30 km s −1 (Mohanty & Basri 2003;Zapatero Osorio et al 2006;Reiners & Basri 2008;Blake et al 2010;Reiners & Basri 2010;Konopacky et al 2012;Deshpande et al 2012). All dwarfs are observable from northern astronomical observatories and sufficiently bright at near-infrared wavelengths to achieve accurate polarimetric photometry (σ P ≤ 0.2%) using short exposures and 4-m class telescopes.…”
Section: Target Selectionmentioning
confidence: 99%
“…As seen from the figure, our sample includes some of the fastest ultracool rotators known to date. In the target sample, there are three binary dwarfs, of which two (LP 349−25AB and LP 415−20AB) are resolved, and v sin i values are available for each component separately (Konopacky et al 2012). The components of the pairs have similar spectral types (Table 1) and magnitudes: ΔJ = 0.84 ± 0.15 mag for LP 415-20 (Siegler et al 2003), and ΔJ = 0.35 ± 0.03 mag for LP 349-25 (Dupuy et al 2010).…”
Section: Target Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, L dwarfs are known to be fast rotators with spectroscopic rotational velocities ranging from ∼10 through ∼90 km s −1 at nearly one-third of the break-up velocity (Konopacky et al 2012, and references therein). By adopting a radius of 0.1-0.3 R , which is the size predicted for L-type sources with ages between 50 Myr and a few Gyr by evolutionary models (Chabrier et al 2000), the expected rotation periods of our targets lie in the interval 1-35 h. Our data do not sample these short periods of time, rather they cover hundreds (>750) to tens of thousands of rotation loops.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%